The Impact of Sustainable Development Goals on Local and Community Networks and Opportunities - Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Abdul Latif, Azmi; Jamaludin, Maisarah Auni (Journal of Technical Education and Training, 2024)
The Sustainable Development Goals (SDGs) serve as a comprehensive blueprint for achieving a more sustainable and equitable future by 2030. These 17 global goals encompass various objectives, including poverty alleviation, environmental sustainability, and social inclusion. This paper aims to analyze the impact of the SDGs on local and community engagement in Malaysia, examining the role of networks in facilitating sustainable development at the grassroots level. The methodology used in this study is a multistage evaluation with a combination of quantitative and qualitative analysis. In this project, the use of ROV is much more accurate and transparent to measure the impact of the project in terms of beneficiaries’ satisfaction (deep), new skills acquired (clear), processes and procedures in place (system, formation of relationships/network (wide), gender consideration (gender), as well as long-term sustainability (SDG). The finding shows that evaluated projects offer beneficiaries opportunities to enhance and expand their community networking and foster strategic partnerships, joint actions, and shared priorities regarding the same goal.